Answer: To find the inverse of the function, we need to make x as a function of y and at the final step make a switch between x and y (i.e. make x as y and y as x)
y = x² + 4x + 4 ⇒⇒⇒ factor the quadratic equation
y = (x+2)(x+2)
y = (x+2)² ⇒⇒⇒ take the square root to both sides
√y = x+2
x = √y - 2 ⇒⇒⇒ x becomes a function of y
final step:
∴ y = √x - 2 ⇒⇒⇒ the inverse of the given function
So, as a conclusion:
f(x) = y = x² + 4x + 4 ⇒⇒⇒ the given function
f⁻¹(x) = y = √x - 2 ⇒⇒⇒ the inverse of the given function
Answer:
C
Step-by-step explanation:
4x-5+x=180. Add 5 to both sides
5x=185. Divide by 6
X=37
180-37=143
143
Answer:
Step-by-step explanation:
0.5bh = 36
0.5(5b)(5h) = 25(0.5bh) = 25 × 36 = 900 sq cm
Answer:
Step-by-step explanation: PURPLE
Hey there!
All we need to do is multiply the unit price of the pencil ($.35) by how many pencils she wants to buy (4)
$.35 x 4 = $1.40
Therefore, she will pay $1.40 for 4 pencils
Hope this helps you!
God bless ❤️
xXxGolferGirlxXx